HCI International 2016 – Posters' extended abstracts : 18th International Conference, HCI International 2016, Toronto, Canada, July 17-22, 2016, Proceedings.: 18th International Conference, HCI International 2016, Toronto, Canada, July 17-22, 2016, Proceedings. Part I ([2016]) - Unknown
No abstract available